2019
DOI: 10.1002/ente.201900016
|View full text |Cite
|
Sign up to set email alerts
|

Impurities in Primary Coolant Salt of FHRs: Chemistry, Impact, and Removal Methods

Abstract: The fluoride salt‐cooled high‐temperature reactor (FHR) is one of the Gen. IV reactor concepts. Considering the complexity of salt chemistry, radiation risk, impurity‐induced material corrosion, and impurity‐induced solid precipitation, the salt chemistry should be well controlled. Therefore, molten salt cleanup systems are needed in operation. Based on the experience of molten salt reactors (MSRs) and available data, the present study identifies the types of impurities, their potential sources, and their impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…While previous studies have found that impurities can signicantly increase in corrosion and change the thermochemical properties of salt, the specic impact of different impurities on tritium is not well understood. 8,9 Here, additional simulations were performed for tritium and Flibe in the presence of a single unit of Cr (dominant corrosion product) and H 2 O (atmospheric moisture) at 973 K. In these cases, tritium diffusivity decreased by 25% and 15% respectively. From structure analysis, tritium was found to coordinate with the impurities (Cr-3 H and 3 H-O bonding), which likely resulted in the observed differences in diffusivity relative to pure Flibe.…”
Section: Tritium Diffusivity In Flibe and Flinakmentioning
confidence: 99%
See 3 more Smart Citations
“…While previous studies have found that impurities can signicantly increase in corrosion and change the thermochemical properties of salt, the specic impact of different impurities on tritium is not well understood. 8,9 Here, additional simulations were performed for tritium and Flibe in the presence of a single unit of Cr (dominant corrosion product) and H 2 O (atmospheric moisture) at 973 K. In these cases, tritium diffusivity decreased by 25% and 15% respectively. From structure analysis, tritium was found to coordinate with the impurities (Cr-3 H and 3 H-O bonding), which likely resulted in the observed differences in diffusivity relative to pure Flibe.…”
Section: Tritium Diffusivity In Flibe and Flinakmentioning
confidence: 99%
“…O ¼ 0:6 0:4 0:4 0:6 ; T ¼ 1 À t p t p t p 1 À t p (8) The transition probability of switching states, t p was set between 10 À6 to 10 À7 , which is markedly low to provide a stronger noise lter that removes false transitions in the observed signal. This is necessary due to the high-temperature liquid state causing high-frequency uctuations in the system.…”
Section: Atomic Coordination and Complexation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A eutectic mixture LiF-NaF-KF (FLiNaK, 46.5LiF-11.5NaF-42KF, mol%) was proposed as a promising coolant in molten salt reactor applications [131]. Some studies focused on the corrosion of materials and reprocessing fission products in FLiNaK melts.…”
Section: Thermodynamic Evaluation Of the Feasibility Of Flinak Electrolyte For Ree Recoverymentioning
confidence: 99%